Sensitive poetics about the path: a walk through intangible heritage - Kumm, Rosely; Brambati, Alice (Revista do Colóquio, 2024)
Preserving the memory of cultural events through constructs that commemorate, narrate, or safeguard is a practice relevant to all human societies. With this same intention, the present account describes an experience in the field during the traditional walk of the "Passos de Anchieta," aiming to highlight how Public Art and its corresponding manifestations of intangible culture can influence spatial perception and strengthen the connection between the community and the local landscape.